2007
DOI: 10.1017/s0967199407004236
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of fructose in chemically defined protein-free medium enhances the in vitro development of bovine transgenic cloned embryos

Abstract: The present study evaluated the possible embryotrophic role of fructose supplementation in chemically defined protein-free KSOM on in vitro development of bovine transgenic cloned embryos. Bovine fetal fibroblasts transfected with expression plasmids for bovine prion protein (PrP) mutant gene with GFP marker gene were used as donor nuclei for reconstruction of slaughterhouse-derived in vitro matured oocytes. The reconstructed oocytes were cultured in KSOM supplemented with 0.01% PVA (KSOM-PVA) at 39 degrees C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Thus, the present hypothesis of the synergistic effect of glucose and fructose in the culture medium might be a logical approach. Most recently, Bhuiyan et al [31] reported that combined glucose and fructose supplementation in the culture medium significantly increased blastocyst formation in bovine transgenic cloned embryos. The expression of Glut5, which has a high affinity for fructose, indicates that the early embryo is capable of transporting this energy substrate [18].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present hypothesis of the synergistic effect of glucose and fructose in the culture medium might be a logical approach. Most recently, Bhuiyan et al [31] reported that combined glucose and fructose supplementation in the culture medium significantly increased blastocyst formation in bovine transgenic cloned embryos. The expression of Glut5, which has a high affinity for fructose, indicates that the early embryo is capable of transporting this energy substrate [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the glycosaminoglycan and type II collagen levels were higher in the serum-free medium than those in the serumsupplemented medium, and the final cell-matrix development was indentified to be suitable (Reza and Nicoll, 2010). Bhuiyan et al (2007) added glucose and fructose to a protein-free serum-free medium for oocytes and determined the ratio of the medium required to optimize the development of bovine transgenic cloned embryos. Studies have also been conducted to reveal that oocyte growth and activation can be induced by the addition of activin or folliclestimulating hormone, even without serum (McLaughlin and Telfer, 2010).…”
Section: Replacing or Removing Fbs In Cell Culture Mediamentioning
confidence: 97%
“…A primary activation treatment with electric stimulus, ethanol, ionomycin or calciumionophore induces a rise of the Ca 2+ concentration in oocytes; with strontium, it induces calcium oscillation. Among these primary activation treatments, bovine oocytes are mainly activated with ionomycin after reconstruction [28][29][30]. Ikumi et al [10] used ionomycin as the primary activation treatment for generation of Antarctic minke whale iSCNT embryos using bovine cytoplasts with an adequate proportion (71-86%) of PPN formation.…”
Section: Production Of Sei Whale Cloned Embryosmentioning
confidence: 99%